2022
DOI: 10.35848/1882-0786/aca751
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction of crack propagation in the strained SiGe/Ge(111) induced by the local growth on the depth-controlled area patterning

Abstract: We propose a method for obtaining crack-free fully-strained SiGe layers on Ge(111). To achieve the crack-free strained SiGe layers, we introduce patterned area with a sufficient depth (step height) of more than 1 µm on Ge(111) substrates. Because of the complete suppression of the crack propagation from the SiGe layer grown on the outside of the patterned area on Ge(111), we achieve crack-free fully strained SiGe layers on the inside of the patterned area. This approach will drastically expand applicability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that defects such as ridges and cracks are prevented from propagating by etching at sufficient depth to form a mesa pattern and growing a SiGe layer. 31,32) By applying such a technique, it is expected that high-performance devices can be fabricated efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that defects such as ridges and cracks are prevented from propagating by etching at sufficient depth to form a mesa pattern and growing a SiGe layer. 31,32) By applying such a technique, it is expected that high-performance devices can be fabricated efficiently.…”
Section: Resultsmentioning
confidence: 99%